Effect of climatic factors on the phenological phases of Mauritia flexuosa Lf. in low terrace plantations in Ucayali, Peru - Revilla-Chávez, Jorge Manuel (2021)
The aim of this study was to determine the influence of air temperature and rainfall on the phenological development of Mauritia flexuosa in plantations located in Ucayali, Peru. For this, during a 24-month period, 191 19-year-old palm trees were evaluated, distributed in three plantations established on low terrace soils. The results showed that the 45% of palm trees did not manifest their sexual maturity, meanwhile, 42% and 13% of individuals with male and female sex, respectively, were verified. It was found that the phenological cycle was biannual, with overlapping phenophases and staggered events. In female individuals, maximum flowering was observed in phenophase FLA1 (4-5%) from September to November 2018 and maximum fruiting FRM1 (4-6%) from October 2018 to January 2019; In male individuals, the FLA2 flowering phenophase occurs in two periods between September 2018 and February 2020, meanwhile, the open flower phenophase of both sexes is synchronous in a higher proportion between September and November. It was determined that pluvial precipitation and air temperature (maximum and minimum) did not show correlation (p ≤ 0.05) with the productive phenophases of Mauritia flexuosa. The pluvial precipitation, the maximum temperature and the minimum air temperature showed null association with each one of the phenological phases of the Mauritia flexuosa palm trees during the evaluation period. In order to obtain information for the planning of silvicultural management activities for the conservation of the species, it is recommended to evaluate for more years the influence of climatic elements on the productive development of Mauritia flexuosa.